Pressure Prediction of Electronic, Anisotropic Elastic, Optical, and Thermal Properties of Quaternary (M2/3Ti1/3)3AlC2 (M = Cr, Mo, and Ti) - Liang Sun; Yimin Gao; Yangzhen Liu; Guoliang Wang; Yiran Wang; Wenyan Zhai; Wen Wang (Advances in Condensed Matter Physics)
The electronic, mechanical, anisotropic elastic, optical, and thermal properties of quaternary (M2/3Ti1/3)3AlC2 (M = Cr, Mo, and Ti) under different pressure are systematically investigated by first-principles calculations. The bonding characteristics of these compounds are the mixture of metallic and covalent bonds. With an increase of pressure, the heights of total density of states (TDOS) for these compounds decrease at Fermi level. The highest volume compressibility among three compounds is Mo2TiAlC2 for its smallest relative volume decline. The relative bond lengths are decreasing when the pressure increases. The bulk and shear modulus of the one doped with Cr or Mo are larger than those of Ti3AlC2 with pressure increasing. With an increase of pressure, the anisotropy of these compounds also increases. Moreover, Mo2TiAlC2 has the biggest anisotropy among the three compounds. The results of optical functions indicate that the reflectivity of the three compounds is high in visible-ultraviolet region up to ~10.5 eV under ambient pressure and increasing constantly when under pressure. Mo2TiAlC2 has the highest loss function. The calculated sound velocity and Debye temperature show that they all increase with pressure. CV of the three compounds is also calculated.